The violation of the patrimonial rights of the members of de facto unions due to the lack of a municipal registry of de facto unions in the Province of Tacna, 2011 - Miranda Pérez, Sandra (2014)
Objective: Determine how they affect the economic rights and economic security of the cohabitants and their families not being incorporated into a municipal register of unions. And demonstrate the need for regulation through alternative means that can improve the way you test the convivial relationship, could be an ideal means the municipal register. Methods: To investigate the cases we have used the survey technique. And the instrument to obtain the data required to carry out the development of the research was obtained through questionnaires. The sample was taken during the month of February 2013 in the city of Tacna, from February 02 to February 26. The research is the type of applied research, because change aims of the legal system, so the aim of the research is to try to provide items to alter reality. The research design to be measured by its location in time is a cross-sectional research. Results: The results presented confirm that there is a significant relationship between the lack of a record of couples who maintain a common-law and the violation of fundamental property rights of cohabitants, since the lack of accuracy, comprehensiveness of verified limits accuracy in determining the start time for the recognition of common-law relationship conspires against the property rights of cohabitants. Therefore, the lack of a record of couples who maintain a de facto union violates his fundamental property rights of cohabitants, so that a viable proposal Municipal Unions Registration indeed prove an effective instrument to safeguard the property rights of cohabitants. Conclusions: The results allowed to confirm that there is a significant relationship between the lack of a record of couples who maintain a common-law and the violation of fundamental property rights of cohabitants.